Cable optimization of a cable-stayed bridge based on genetic algorithms and the influence matrix method. Issue 1 (2nd January 2022) - Feng, Yue; Lan, Cheng; Briseghella, Bruno; Fenu, Luigi; Zordan, Tobia
Abstract : Structural optimization is an important tool for structural designers that helps them to find innovative design solutions and structural forms with a better exploitation of materials as well as decreased self-weight and minimum material costs. In this article, a design procedure coupling the influence matrix method and genetic algorithms to optimize stay cables in cable-stayed bridges is presented. Following that, the design procedure is utilized in the preliminary design of a twin towers double-cable planes cable-stayed bridge to be located in Ferrara, Italy. The cable cross-sectional areas and corresponding pre-tension forces are optimized simultaneously. The results demonstrate that the proposed procedure is a powerful tool for designing stay cables and predicting the optimum cross-sectional areas of stay cables under certain stress and displacement constraints.